Chronic Atrial and Ventricular Pacing in the Mouse: Application to Model Cardiac Dyssynchrony and Resynchronization in Heart Failure. (February 2019) - Ståhlberg, Marcus; Nakagawa, Ryo; Bedja, Djahida; Zhu, Guangshuo; Lin, Brian L.; Saberi, Amir; Lee, Dong I.; Kass, David A.
Abstract : Background: The mouse is the most widely used mammal in experimental biology. Although many clinically relevant in vivo cardiac stressors are used, one that has eluded translation is long-term cardiac pacing. Here, we present the first method to chronically simulate and simultaneously record cardiac electrical activity in conscious mobile mice. We then apply it to study right ventricular pacing induced electromechanical dyssynchrony and its reversal (resynchronization). Methods and Results: The method includes a custom implantable bipolar stimulation and recording lead and flexible external conduit and electrical micro-commutator linked to a pulse generator/recorder. This achieved continuous pacing for at least 1 month in 77% of implants. Mice were then subjected to cardiac ischemia/reperfusion injury to depress heart function, followed by 4 weeks pacing at the right ventricle (dyssynchrony), right atrium (synchrony), or for 2 weeks right ventricle and then 2 weeks normal sinus (resynchronization). Right ventricular pacing–induced dyssynchrony substantially reduced heart and myocyte function compared with the other groups, increased gene expression heterogeneity (>10 fold) comparing septum to lateral walls, and enhanced growth and metabolic kinase activity in the late-contracting lateral wall. This was ameliorated by restoring contractile synchronization. Conclusions: The new method to chronically pace conscious mice yields stable atrial and ventricular capture and a means to dissect basic mechanisms of electromechanical physiology and therapy. The data on dyssynchrony and resynchronization in ischemia/reperfusion hearts is the most comprehensive to date in ischemic heart disease, and its similarities to nonischemic canine results support the translational utility of the mouse. Abstract : Supplemental Digital Content is available in the text.